The infographic genre in English high school textbooks: a multimodal analysis - Daxo, Haylanne Clésia Pereira; Alencar, Maria Joyce Gomes; Oliveira, Larisse Carvalho de (Entrepalavras, 2025)
The present study analyzes how high school English textbooks promote multiliteracies skills. The specific objectives consist first of investigating in what way the question texts of the infographics collected indicate the need for visual literacy, then inspecting how the question texts guided the multimodal reading and writing, and finally verifying if the multimodal resources are required to support the resolution of the texts. The main theory is the Grammar of Visual Design by Kress and Van Leeuwen (2021). Concerning the methodology, we begin with the selection of the textbooks collection, which is Joy (2020), English Vibes for Brazilian Learners (2020), and Take Action (2020). Subsequently, we collected all the textbook activities that contained the infographic genre, totaling twenty-one. Finally, we analyze all the infographics collected. The results revealed that all the infographics analyzed promote multiliteracies skills effectively. We verified that the development of multiliteracies abilities occurs because of the multimodal resources of the infographics and the variation of significant topics approached in the multi-semiotics texts.